New Trends in Catalysis for Sustainable CO2 Conversion - Ereña Loizaga, Javier; Ateka, Ainara (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue on "New Trends in Catalysis for Sustainable CO2 Conversion", released in the Catalysts open access journal, shows new research about the development of catalysts and catalytic routes for CO2 valorization, in addition to the optimization of the reaction conditions for the process. This issue includes ten articles and three reviews about different innovative processes for CO2 conversion.Carbon capture and storage (CCS) is a physical process consisting of the separation the CO2 (emitted by industry and the combustion processes for energy generation) and its transportation to geological storage isolates it from the atmosphere in the long term. However, the most promising routes for CO2 mitigation are those pursuing its catalytic valorization. By applying specific catalysts and suitable operating conditions, CO2 molecules react with other components to form longer chains (i.e., hydrocarbons). Accordingly, effort should be made to catalytically valorize CO2 (alone or co-fed with syngas) as an alternative way of reducing greenhouse gas emissions and obtaining high-value fuels and chemicals. Carbon capture and utilization (CCU) is a developing field with significant demand for research in the following aspects:The development of new catalysts, catalytic routes, and technologies for CO2 conversion;The study of new processes for obtaining fuels and chemicals from CO2;Optimization of the catalysts and the reaction conditions for these processes;Further steps in advanced processes using CO2-rich feeds (H2+CO2 or CO2 mixed with syngas), increasing product yields.